Changes in body structure of adult football players during one training unit - Colakhodzic, E.; Vidovic, N.; Fazlagic, S. (Homosporticus, 2010)
The aim of this study is to establish the quantitative changes in body structure of 28 professional footballers (Premier League of Bosnia and Herzegovina), caused by a single training session during the preparatory period of the team. Structure of the 90 minute training session consisted of introductory-preparatory, main and final part, being designed to combine game with exercise. The subject of study covered transformational processes of body composition of elite football players of Bosnia and Herzegovina in order to determine the effects of a football training sessions on their physical structure. Partial quantitative changes in body composition, formed during training session, were analyzed by T-test for paired samples. These results indicate that there was a statistically significant difference at the level of significance (p<.01) variables for the estimation of body mass (AMAS), body mass index (BMI), basal metabolic rate (BMR), fat free body part (FFM) and amounts of body water (TBW). Statistically significant differences at the level of significance (p<.05) occurred at the variables for the assessment of resistance in the body (IMPEDANCE). Variables for estimation of height (AVIS), percentage of at in the body (FAT %) and of fat in body weight (FATMAS) showed that there was no statistically significant changes. It can be concluded that 90 minute training session organized in this manner can have significant impact on the transformation of body composition.